Electrodes and electrode assemblies
A coating layer with specific polymer particles and binders addresses the safety issues in lithium secondary batteries by preventing short circuits and enhancing high-temperature performance, improving adhesion and electrolyte impregnation.
Patent Information
- Application Number
- JP2024539056
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-05-31
- Filing Date
- 2023-06-05
- Publication Date
- 2025-01-09
- Estimated Expiration
- 2043-06-05
AI Technical Summary
Lithium secondary batteries face safety risks due to short circuits between the positive and negative electrodes, particularly at high temperatures, caused by the shrinkage of polyolefin-based separation membranes, which can lead to fires.
A coating layer is formed on the electrode active material layer, comprising polymer particles with a zeta potential of 25 mV or more, a dispersant, and a binder, which replaces or supplements the separation membrane, ensuring electrical insulation and preventing short circuits.
The coating layer enhances high-temperature safety and life characteristics of lithium secondary batteries by reducing cracks, improving adhesion, and allowing for better impregnation of flame-retardant electrolytes, thereby preventing short circuits and ensuring excellent safety and electrochemical performance.
Smart Images

Figure 2025500561000001_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0069164 filed on June 7, 2022 and Korean Patent Application No. 10-2023-0070307 filed on May 31, 2023, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference.
[0002] The present invention relates to an electrode capable of improving high-temperature safety and life characteristics of a lithium secondary battery, and an electrode assembly including the same. [Background technology]
[0003] With the technological development and increasing demand for electric vehicles and energy storage systems (ESS), the demand for batteries as energy sources is rapidly increasing, and as a result, research on batteries that can meet various requirements is being conducted. In particular, research on lithium secondary batteries that have high energy density and excellent life and cycle characteristics as a power source for such devices is being actively conducted.
[0004] In general, a lithium secondary battery includes a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, an electrolyte, etc. The positive electrode may generate oxygen due to an unstable structure in a charged state, and when oxygen is generated, there is a high risk of fire. Therefore, research and development are being conducted on methods for improving the safety of lithium secondary batteries.
[0005] The separator is used to ensure electrical insulation between the positive and negative electrodes, and is generally a thin film made of polyolefin. However, polyolefin-based separators tend to shrink in high-temperature environments, and may fail to provide insulation between the positive and negative electrodes. If electrical insulation between the positive and negative electrodes is no longer possible, a short circuit may occur, which may cause fire due to the reaction with oxygen generated by the unstable positive electrode. In other words, if a short circuit occurs in a lithium secondary battery in a charged state in a high-temperature environment, the lithium secondary battery may catch fire.
[0006] Therefore, there is a demand for technological development of a method for improving the high temperature safety of lithium secondary batteries. Summary of the Invention [Problem to be solved by the invention]
[0007] Therefore, the present invention provides an electrode and an electrode assembly including the same, which improves the high-temperature safety and life characteristics of a lithium secondary battery by forming a coating layer that replaces or supplements a separator. [Means for solving the problem]
[0008] One embodiment of the invention is an electrode comprising an electrode active material layer and a coating layer formed on the electrode active material layer, The coating layer includes polymer particles having an absolute value of a zeta potential of 25 mV or more; a dispersant; and a binder, the binder including at least one selected from the group consisting of polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone (PVP), polyethylene (PE), polypropylene, ethylene-propylene-diene polymer, and sulfonated ethylene-propylene-diene polymer, the binder being included in an amount of 12 wt % to 32 wt % based on the total weight of the coating layer.
[0009] Another embodiment of the present invention is an electrode assembly including a first electrode, a second electrode, and a coating layer disposed between the first electrode and the second electrode, The coating layer includes polymer particles having an absolute value of a zeta potential of 25 mV or more; a dispersant; and a binder, the binder including at least one selected from the group consisting of polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone (PVP), polyethylene (PE), polypropylene, ethylene-propylene-diene polymer, and sulfonated ethylene-propylene-diene polymer, and the binder is included in an amount of 12 wt% to 32 wt% based on the total weight of the coating layer. Effect of the Invention
[0010] The electrode and electrode assembly according to the present invention has a coating layer of a predetermined composition formed on the electrode to replace or supplement an existing separator, thereby ensuring electrical insulation between the electrodes.
[0011] As a result of the inventors' experiments, it was confirmed that damage such as cracks in the coating layer was significantly reduced by optimizing the composition of the coating layer. Therefore, when a lithium secondary battery including the electrode assembly is charged, micro-shorts between the positive and negative electrodes that may occur due to localized concentration of lithium ions in the cracks in the coating layer are prevented, and as a result, the charging time of the battery is shortened and the safety of the battery is improved.
[0012] In addition, the electrode and electrode assembly including the coating layer can suppress the occurrence of short circuits caused by shrinkage of the existing separator, and can reduce the risk of fire due to high temperature or external impact. In particular, the coating layer has better adhesion to the active material layer than the polyolefin-based substrate of the existing separator, and the polymer particles included in the coating layer can have a higher melting point than the polyolefin-based substrate. Therefore, by replacing or supplementing the existing separator with such a coating layer, the coating layer does not easily shrink even in a high-temperature environment, preventing short circuits between electrodes, and improving the high-temperature safety of the battery.
[0013] In addition, when a flame-retardant electrolyte is used to ensure the high-temperature safety of a lithium secondary battery, the coating layer can exhibit higher impregnation of the flame-retardant electrolyte than the polyolefin-based substrate of the existing separator, thereby ensuring high lithium ion mobility along with excellent safety.
[0014] Therefore, the electrode and electrode assembly of the present invention can greatly contribute to achieving excellent electrochemical properties such as excellent high-temperature safety and improved life characteristics of lithium secondary batteries. [Brief description of the drawings]
[0015] [Figure 1] 1 is a photograph showing the surface of the inner-electrode coating layer produced in Example 1. [Diagram 2] 1 is a photograph showing the surface of the inner-electrode coating layer produced in Example 2. [Diagram 3] 1 is a photograph showing the surface of an inner-electrode coating layer produced in Comparative Example 1. [Figure 4] 1 is a photograph showing the surface of an inner-electrode coating layer produced in Comparative Example 2. [Diagram 5] 1 is a graph showing the capacity retention rate of lithium secondary batteries including the electrodes produced in Example 1 and Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Unless otherwise defined, all terms (including technical and scientific terms) used herein are used in the sense commonly understood by those having ordinary skill in the art to which the present invention belongs. Furthermore, terms defined in commonly used dictionaries are not to be interpreted ideally or excessively unless otherwise clearly and specifically defined.
[0017] The terms used in the present specification are for the purpose of describing the embodiments, and are not intended to limit the present invention. In the present specification, the singular form includes the plural form unless otherwise specified in the text. The words "comprises" and / or "comprising" used in the specification do not exclude the presence or addition of one or more other components in addition to the components mentioned.
[0018] In this specification, when a part includes a certain component, this means that it can further include other components, not excluding other components, unless specifically stated to the contrary.
[0019] In this specification, the phrase "A and / or B" means "A", or "B", or "A and B".
[0020] In this specification, "%" means % by weight, unless expressly indicated otherwise.
[0021] In this specification, D 50 D means a particle size corresponding to 50% of the cumulative volume in the particle size distribution curve. 50 can be measured by using, for example, a laser diffraction method. The laser diffraction method generally allows measurement of particle sizes from the submicron range to several mm, and can provide results with high reproducibility and high resolution.
[0022] In this specification, the "specific surface area" is measured by the BET method, and specifically, is calculated from the amount of nitrogen gas adsorption at liquid nitrogen temperature (77K) using a BELSORP-mini II manufactured by BEL Japan.
[0023] In this specification, "zeta potential" is an index showing the degree of surface charge of a particle. In the present invention, the zeta potential of a particle can be measured by electrophoretic light scattering using a dynamic light scattering device. Specifically, the polymer particles can be dispersed in water or an alcohol-based solvent without a dispersant, and then the zeta potential value of the particles can be measured by electrophoretic light scattering.
[0024] Hereinafter, electrodes and electrode assemblies according to embodiments of the present invention will be described in detail.
[0025] <Electrode> According to an embodiment of the present invention, there is provided an electrode comprising an electrode active material layer and a coating layer formed on the electrode active material layer. The coating layer comprises polymer particles having an absolute value of a zeta potential of 25 mV or more, a dispersant and a binder. The binder comprises at least one selected from the group consisting of polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone (PVP), polyethylene (PE), polypropylene, ethylene-propylene-diene polymer and sulfonated ethylene-propylene-diene polymer. The binder is contained in an amount of 12% by weight to 32% by weight based on the total weight of the coating layer.
[0026] It is known that existing separators made of polyolefin-based materials are prone to thermal shrinkage at high temperatures, which can lead to short circuits between the positive and negative electrodes, thereby reducing the high-temperature safety of lithium secondary batteries.
[0027] In one embodiment of the electrode, a coating layer that replaces or supplements such an existing separator is formed on an electrode active material layer, and the coating layer includes a certain type and content of a binder, polymer particles that satisfy a certain range of zeta potential, and the like.
[0028] The absolute value of the zeta potential can define the surface polarity of the polymer particles, and having an absolute value above a certain level can mean that the surface polarity is high. It has been confirmed that by combining polymer particles with high surface polarity with a binder of a specific composition, the coating layer not only exhibits porosity, good coating properties and surface characteristics that can replace a separator, but also that the coating layer is substantially free of cracks.
[0029] In addition, since the polymer particles may have a relatively high melting point, when a coating layer including the polymer particles is applied, short circuits caused by the shrinkage of an existing separator can be suppressed, making it possible to provide a lithium secondary battery with improved high temperature safety.Moreover, it has been confirmed that the capacity retention rate and life characteristics of a lithium secondary battery can be further improved by adjusting the content range of the binder in the coating layer and the content range of the polymer particles excluding the binder.
[0030] In addition, the coating layer can improve the impregnation of the flame-retardant electrolyte, which will be described later, compared to existing separators. This is believed to be because the flame-retardant electrolyte has a relatively high polarity compared to existing electrolytes. Therefore, by combining the electrode of the embodiment with a flame-retardant electrolyte, the safety of the lithium secondary battery can be further improved, while ensuring high lithium ion mobility due to the coating layer, thereby further improving the electrochemical properties of the battery.
[0031] In the electrode of the embodiment, the coating layer is formed on an electrode active material layer, which will be described later. For example, the coating layer is formed on a positive electrode active material layer or a negative electrode active material layer.
[0032] In the coating layer, the polymer particles may be particles that have a surface charge, and the surface charge and surface polarity are defined by the absolute value range of the zeta potential. Specifically, the zeta potential is a physical property that defines the electrostatic repulsion or dispersibility between the polymer particles, and polymer particles with a large absolute value of the zeta potential can be uniformly dispersed on the electrode to exhibit good and uniform coating properties, and a plurality of fine and uniform pores that allow lithium ions to pass are defined between the particles. In addition, the coating layer can exhibit excellent impregnation with a flame-retardant electrolyte containing a flame-retardant solvent having a relatively large polarity by using polymer particles that satisfy the zeta potential.
[0033] The zeta potential of the polymer particles can be measured, for example, by electrophoretic light scattering using a dynamic light scattering device. In this case, the zeta potential can be measured in a state where the polymer particles are dispersed in water or an alcohol-based solvent without a separate dispersant. In a specific example, the zeta potential can be measured in a state where the polymer particles are dispersed in a water solvent at a concentration of 0.1 wt % or less.
[0034] The absolute value of the zeta potential of the polymer particles may be 25 mV or more, or 35 mV or more, or 45 mV or more, and may be 100 mV or less, or 90 mV or less, or 80 mV or less. When the absolute value of the zeta potential satisfies the above numerical range, the flame-retardant electrolyte can be easily impregnated into the coating layer, and a uniform reaction occurs throughout the electrode, thereby improving various performances such as the capacity, output, and life characteristics of the lithium secondary battery.
[0035] Specific examples of the polymer particles may include, but are not limited to, one or more selected from the group consisting of polyalkyl(meth)acrylates such as polyethylene oxide (PEO), polyphenylene sulfide (PPS), polymethyl(meth)acrylate (PMMA), polystyrene, polyvinyl chloride, polycarbonate, polysulfone, polyethersulfone, polyetherimide, polyphenylsulfone, polyamideimide, polyimide, polybenzimidazole, polyetherketone, polyphthalamide, polybutylene terephthalate, and polyethylene terephthalate.
[0036] The zeta potential of the polymer particles can be adjusted not only by the type of each particle, but also by the particle size or surface properties of the particles. Therefore, in order to achieve the zeta potential, dispersibility, or appropriate porosity of the porous coating layer of the polymer particles, the polymer particles have an average particle size D of 50 nm to 3 μm, or 50 nm to 2 μm, or 100 nm to 1.5 μm. 50 may have the following structure:
[0037] The average particle size D of the polymer particles 50 If the average particle diameter D of the polymer particles is less than 50 nm, the particles will aggregate due to the reduced dispersibility of the particles, and the pores will be clogged by the aggregated particles, making it difficult to form a coating layer having a porous structure. 50 If the thickness is greater than 3 μm, the pore structure in the coating layer becomes simplified, which may cause lithium dendrites to be generated during cell fabrication.
[0038] In addition, in order to control the surface properties of the polymer particles and thereby adjust the zeta potential, the polymer particles are included in the coating layer in a state where they are surface-treated with oxygen plasma or ion beams.
[0039] The polymer particles are contained in an amount of 55% to 85% by weight, 55% to 80% by weight, or 65% to 75% by weight based on the total weight of the coating layer. When the amount of the polymer particles is within the above range, the dispersibility of the particles in the coating layer is improved, and pores are uniformly formed in the coating layer, thereby significantly reducing cracks on the surface of the coating layer.
[0040] Meanwhile, the dispersant prevents the polymer particles from being excessively aggregated in the coating layer, allowing the polymer particles to be effectively dispersed and present in the coating layer.
[0041] Such a dispersant may include a hydrogenated nitrile polymer, specifically a hydrogenated nitrile copolymer, and more specifically a hydrogenated nitrile butadiene rubber (H-NBR).
[0042] The hydrogenated nitrile copolymer may be a copolymer containing α,β-unsaturated nitrile-derived structural units and hydrogenated conjugated diene-derived structural units, or a copolymer containing α,β-unsaturated nitrile-derived structural units, conjugated diene-derived structural units, and hydrogenated conjugated diene-derived structural units. Specifically, the hydrogenated nitrile copolymer may be a hydrogenated nitrile copolymer in which all of the conjugated diene-derived structural units are hydrogenated and no conjugated diene-derived structural units are contained, or, differently, a partially hydrogenated nitrile copolymer in which some of the conjugated diene-derived structural units are hydrogenated and hydrogenated conjugated diene-derived structural units are contained together with the conjugated diene-derived structural units.
[0043] The hydrogenation method of the conjugated diene is carried out by a hydrogenation reaction known in the art, for example, a catalytic hydrogenation reaction using a catalyst system such as Rh, Ru, Pd, or Ir, and the hydrogenation rate can be adjusted by adjusting the amount of catalyst, reaction hydrogen pressure, reaction time, etc.
[0044] The hydrogenated nitrile copolymer can be produced by copolymerizing an α,β-unsaturated nitrile monomer with a conjugated diene monomer, and then hydrogenating the C=C double bond in the copolymer. The polymerization reaction and hydrogenation process of the monomers are carried out by a conventional method.
[0045] As the α,β-unsaturated nitrile monomer, for example, acrylonitrile or methacrylonitrile can be used, and one or more of these can be used as a mixture. As the conjugated diene monomer, for example, a conjugated diene monomer having 4 to 6 carbon atoms, such as 1,3-butadiene, isoprene, or 2,3-methylbutadiene can be used, and one or more of these can be used as a mixture.
[0046] The α,β-unsaturated nitrile-derived structural unit is contained in the hydrogenated nitrile copolymer in an amount of 20% by weight to 50% by weight, or 30% by weight to 40% by weight. When this range is satisfied, the affinity between the hydrogenated nitrile copolymer and an organic solvent (e.g., N-methyl-2-pyrrolidone (NMP)) serving as a medium for forming a coating layer is at an appropriate level, so that the dispersion of polymer particles in the composition for forming a coating layer becomes easier. As a result, pores are uniformly formed in the coating layer, and cracks on the surface of the coating layer can be significantly reduced.
[0047] The hydrogenated nitrile copolymer may have a weight average molecular weight of 5,000 g / mol to 700,000 g / mol, or 5,000 g / mol to 600,000 g / mol, or 10,000 g / mol to 500,000 g / mol. When the weight average molecular weight of the hydrogenated acrylonitrile-butadiene rubber (H-NBR) satisfies the above numerical range, the polymer particles can be uniformly dispersed in the coating layer.
[0048] The above-mentioned dispersant is included in an amount of 3 wt% to 20 wt%, 5 wt% to 20 wt%, or 5 wt% to 15 wt% based on the total weight of the coating layer. When the content of the dispersant satisfies the above range, the dispersibility of the particles included in the coating layer is improved and pores are uniformly formed in the coating layer, thereby significantly reducing cracks on the surface of the coating layer.
[0049] On the other hand, the binder contained in the coating layer serves to improve the adhesive strength between the above-mentioned polymer particles and coating layer and the electrode active material layer.
[0050] The binder may include at least one selected from the group consisting of polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone (PVP), polyethylene (PE), polypropylene, ethylene-propylene-diene polymer, and sulfonated ethylene-propylene-diene polymer, and may not include at least one selected from the group consisting of polytetrafluoroethylene (PTFE), carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), and fluororubber. When the type of binder satisfies the above conditions, a coating layer having excellent adhesive strength is formed on the surface of the electrode, and damage such as cracks on the surface of the coating layer may be significantly reduced.
[0051] The binder is included in an amount of 12 wt% to 32 wt%, 12 wt% to 28 wt%, 15 wt% to 28 wt%, or 15 wt% to 25 wt% based on the total weight of the coating layer. If the binder content is less than 12 wt% based on the total weight of the coating layer, the adhesion between the polymer particles and the electrode active material layer is reduced, causing the coating layer to detach from the electrode active material layer, resulting in damage such as cracks in the coating layer. In addition, if the binder content exceeds 32 wt% based on the total weight of the coating layer, the resistance of the coating layer increases due to the increase in the binder content, which increases the cell resistance and reduces the life performance of the cell.
[0052] The coating layer may have a thickness of 5 μm to 50 μm, or 10 μm to 45 μm, or 15 μm to 40 μm, and may include a plurality of pores having a diameter of 10 nm or more, or 20 nm to 3 μm, or 50 nm to 1 μm, in order to exhibit excellent impregnation with a flame-retardant electrolyte, effectively replace the role of a separator, and reduce the resistance of the coating layer. In this case, the thickness of the coating layer may refer to the total thickness of the coating layer formed on the positive and / or negative electrodes.
[0053] The coating layer may have electrical insulation properties, in which case the coating layer may correspond to, but is not limited to, a porous insulating layer.
[0054] In addition, the coating layer has a characteristic that it does not easily shrink even at high temperatures. Therefore, when an electrode assembly is formed by stacking one or more electrodes including the coating layer without a separate separator, a short circuit between the positive and negative electrodes can be prevented even in a high-temperature environment, thereby improving the high-temperature safety of the electrode assembly.
[0055] In the electrode according to the embodiment described above, the coating layer formed on the electrode active material layer may have excellent surface quality with significantly reduced damage such as cracks. Therefore, when an electrode assembly is formed by stacking one or more electrodes including the coating layer without a separate separator and a lithium secondary battery is manufactured from the electrode assembly, a micro-short circuit phenomenon between the positive electrode and the negative electrode may be prevented.
[0056] According to an embodiment, the coating layer is formed by coating a composition for forming an electrode coating layer on an electrode active material layer and drying the composition.
[0057] In this case, the solid content of the composition for forming an electrode coating layer may be 19 wt% to 25 wt%, or 19 wt% to 23 wt%, or 19 wt% to 21 wt%. Here, the solid content is defined as the total content of components including the above-mentioned polymer particles, binder, and dispersant, excluding a liquid medium such as an organic solvent for dissolving or dispersing these components. When the solid content of the composition for forming an electrode coating layer satisfies the above numerical range, the composition for forming an electrode coating layer may have a viscosity at a level that allows it to be coated on an electrode active material layer.
[0058] Specifically, the viscosity of the composition for forming an electrode coating layer may be 5000 cP to 7000 cP, or 5000 cP to 6800 cP, or 5500 cP to 6800 cP at 25° C. When the viscosity of the composition for forming an electrode coating layer satisfies the above numerical range, the composition for forming an electrode coating layer can be coated on the electrode active material layer with a uniform thickness.
[0059] Meanwhile, in the electrode of the embodiment, the electrode active material layer is formed on an electrode current collector, and the above-mentioned coating layer is formed on the electrode active material layer, and the electrode active material layer and the coating layer are formed in contact with each other without any other layer interposed therebetween.
[0060] When the electrode in the above embodiment is a positive electrode, the positive electrode can include a positive electrode current collector, a positive electrode active material layer formed on the positive electrode current collector, and a coating layer formed on the positive electrode active material layer.
[0061] At this time, the positive electrode current collector may be any material that has conductivity without inducing a chemical change in the battery, and is not particularly limited. For example, as the current collector, stainless steel, aluminum, nickel, titanium, fired carbon, or a material obtained by surface-treating the surface of aluminum or stainless steel with carbon, nickel, titanium, silver, etc. can be used. The positive electrode current collector can have a thickness of 3 μm to 500 μm, and fine irregularities can be formed on the surface of the positive electrode current collector to enhance the adhesion to the positive electrode active material layer. For example, it can be used in various forms such as films, sheets, foils, nets, porous bodies, foams, non-woven fabrics, etc.
[0062] Also, the positive electrode active material layer can contain a positive electrode active material, and can further contain a conductive material, a binder, etc. as required.
[0063] The positive electrode active material is a compound capable of reversible insertion and extraction of lithium, and specifically, can include a lithium metal oxide containing one or more metals such as cobalt, manganese, nickel, or aluminum and lithium. More specifically, the lithium metal oxide is a lithium-manganese-based oxide (e.g., LiMnO2, LiMn2O4, etc.), a lithium-cobalt-based oxide (e.g., LiCoO2, etc.), a lithium-nickel-based oxide (e.g., LiNiO2, etc.), a lithium-nickel-manganese-based oxide (e.g., LiNi 1-Y Mn Y O2 (where 0 < Y < 1), LiMn 2-Z Ni Z O4 (where 0 < Z < 2), etc.), a lithium-nickel-cobalt-based oxide (e.g., LiNi 1-Y1 Co Y1 O2 (where 0 < Y1 < 1), etc.), a lithium-manganese-cobalt-based oxide (e.g., LiCo 1-Y2 MnY2 O2 (where 0 < Y2 < 1), LiMn 2-Z1 Co Z1 O4 (where 0 < Z1 < 2), etc.), lithium-nickel-manganese-cobalt oxide (e.g., Li(Ni p Co q Mn r )O2 (where 0 < p < 1, 0 < q < 1, 0 < r < 1, p + q + r = 1) or Li(Ni p1 Co q1 Mn r1 )O4 (where 0 < p1 < 2, 0 < q1 < 2, 0 < r1 < 2, p1 + q1 + r1 = 2), etc.), or lithium-nickel-cobalt-transition metal (M) oxide (e.g., Li(Ni p2 Co q2 Mn r2 M s2 )O2 (where M is selected from the group consisting of Al, Fe, V, Cr, Ti, Ta, Mg, and Mo, and p2, q2, r2, and s2 are atomic fractions of independent elements, 0 < p2 < 1, 0 < q2 < 1, 0 < r2 < 1, 0 < s2 < 1, p2 + q2 + r2 + s2 = 1), etc.), lithium iron phosphate (e.g., Li 1+a Fe 1-x M x (PO 4-b )X b (where M is one or more selected from Al, Mg, and Ti, X is one or more selected from F, S, and N, -0.5 ≤ a ≤ 0.5, 0 ≤ x ≤ 0.5, 0 ≤ b ≤ 0.1), etc., and one or more of these compounds are included.
[0064] Among these, in terms of enhancing the capacity characteristics and safety of the battery, the lithium metal oxide is LiCoO2, LiMnO2, LiNiO2, lithium nickel manganese cobalt oxide (e.g., Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 )O2, Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.5 Mn 0.3 Co 0.2)O2, Li(Ni 0.7 Mn 0.15 Co 0.15 )O2 and Li(Ni 0.8 Mn 0.1 Co 0.1 )O2), lithium nickel cobalt aluminum oxide (e.g., Li(Ni 0.8 Co 0.15 Al 0.05 )O2), or lithium nickel manganese cobalt aluminum oxide (e.g., Li(Ni 0.86 Co 0.05 Mn 0.07 Al 0.02 )O2), lithium iron phosphate (e.g., LiFePO4), or the like, or a mixture of any one or more of these can be used.
[0065] The positive electrode active material is included in an amount of 60 wt % to 99 wt %, alternatively 70 wt % to 99 wt %, or alternatively 80 wt % to 98 wt %, based on the total weight of the positive electrode active material layer.
[0066] Meanwhile, the conductive material is a component for further improving the conductivity of the positive electrode active material, and the conductive material is not particularly limited as long as it has conductivity without inducing a chemical change in the battery. For example, carbon powder such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black; graphite powder such as natural graphite, artificial graphite, or graphite with a highly developed crystal structure; conductive fibers such as carbon fibers and metal fibers; carbon fluoride powder; conductive powder such as aluminum powder or nickel powder; conductive whiskers such as zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives can be used.
[0067] Typically, the conductive material is included in an amount of 1 wt % to 20 wt %, alternatively 1 wt % to 15 wt %, or alternatively 1 wt % to 10 wt %, based on the total weight of the positive electrode active material layer.
[0068] The binder is a component that assists in bonding between the positive electrode active material and the conductive material, and to the positive electrode current collector.
[0069] Examples of such binders include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polyethylene (PE), polypropylene, ethylene-propylene-diene polymers, sulfonated ethylene-propylene-diene polymers, styrene-butadiene rubber, fluororubbers, and various copolymers.
[0070] Typically, the binder is included in an amount of 1 wt % to 20 wt %, alternatively 1 wt % to 15 wt %, or alternatively 1 wt % to 10 wt %, based on the total weight of the positive electrode active material layer.
[0071] Meanwhile, when the electrode of the embodiment is a negative electrode, the negative electrode may include a negative electrode current collector, a negative electrode active material layer formed on the negative electrode current collector, and a coating layer formed on the negative electrode active material layer. Alternatively, the negative electrode may include a graphite electrode made of carbon (C) and a coating layer formed on the graphite electrode. Alternatively, the negative electrode may include a metal itself and a coating layer formed on the metal.
[0072] The negative electrode current collector is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery, and can be, for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector can usually have a thickness of 3 μm to 500 μm, and like the positive electrode current collector, the surface of the negative electrode current collector can be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, it can be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0073] The negative electrode active material layer may include a negative electrode active material, and may further include a conductive material, a binder, and the like, if necessary.
[0074] The negative electrode active material can include at least one selected from the group consisting of lithium metal, a carbon material capable of reversibly inserting / desorbing lithium ions, a metal, or an alloy of such a metal with lithium, a metal composite oxide, a material capable of doping and dedoping lithium, and a transition metal oxide.
[0075] The carbonaceous material capable of reversibly inserting / extracting lithium ions may be any carbonaceous negative electrode active material commonly used in lithium ion secondary batteries, and representative examples thereof include crystalline carbon, amorphous carbon, or both. Examples of the crystalline carbon include graphite such as amorphous, plate-like, flake-like, spherical, or fibrous natural graphite or artificial graphite, and examples of the amorphous carbon include soft carbon (low-temperature calcined carbon), hard carbon, mesophase pitch carbide, and calcined coke.
[0076] The metal or the alloy of these metals with lithium may be a metal selected from the group consisting of Cu, Ni, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn, or an alloy of these metals with lithium.
[0077] The metal composite oxides include PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, Bi2O5, Li x Fe2O3(0≦x≦1), Li x WO2(0≦x≦1) and Sn x Me 1-x Me' y O z(Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, Group 1, Group 2, Group 3 elements of the periodic table, halogen; 0 < x ≤ 1; 1 ≤ y ≤ 3; 1 ≤ z ≤ 8) can be selected from the group consisting of.
[0078] As the substance capable of doping and undoping lithium, Si, SiO x (0 < x ≤ 2), Si-Y alloy (wherein Y is an element selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and combinations thereof, and is not Si), Sn, SnO2, Sn-Y (wherein Y is an element selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and combinations thereof, and is not Sn), etc. may be mentioned, and at least one of these and SiO2 may be mixed and used. As the element Y, Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof are selected from the group consisting of.
[0079] Examples of the transition metal oxide include lithium-containing titanium composite oxide (LTO), vanadium oxide, lithium vanadium oxide, etc.
[0080] The negative electrode active material is contained in an amount of 60% by weight to 99% by weight, or 70% by weight to 99% by weight, or 80% by weight to 98% by weight based on the total weight of the negative electrode active material layer.
[0081] In addition, the conductive material is a component for further improving the conductivity of the negative electrode active material, and such a conductive material is not particularly limited as long as it has conductivity without inducing a chemical change in the battery, and examples that can be used include carbon powders such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; graphite powders such as natural graphite, artificial graphite, and graphite with highly developed crystal structures; conductive fibers such as carbon fibers and metal fibers; carbon fluoride powder; conductive powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.
[0082] The conductive material is included in an amount of 1 wt % to 20 wt %, alternatively 1 wt % to 15 wt %, or alternatively 1 wt % to 10 wt %, based on the total weight of the negative electrode active material layer.
[0083] The binder is a component that helps to bond the conductive material, the negative electrode active material, and the negative electrode current collector. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polyethylene, polypropylene, ethylene-propylene-diene polymer, sulfonated ethylene-propylene-diene polymer, styrene-butadiene rubber, fluororubber, and various copolymers thereof.
[0084] Typically, the binder is included in an amount of 1 wt % to 20 wt %, alternatively 1 wt % to 15 wt %, or alternatively 1 wt % to 10 wt %, based on the total weight of the negative electrode active material layer.
[0085] When a metal is used without forming a negative electrode active material layer in the negative electrode, the negative electrode may be manufactured by physically bonding, rolling, or depositing a metal thin film or a metal on the negative electrode current collector. The deposition method may be an electrical deposition method or a chemical vapor deposition method.
[0086] For example, the metal thin film itself or the metal bonded / rolled / deposited on the negative electrode current collector may include one metal or an alloy of two metals selected from the group consisting of lithium (Li), nickel (Ni), tin (Sn), copper (Cu) and indium (In).
[0087] <Electrode assembly> Meanwhile, an electrode assembly according to another embodiment of the present invention includes the electrode according to the above-mentioned embodiment. The electrode assembly according to the other embodiment includes a first electrode, a second electrode, and a coating layer disposed between the first electrode and the second electrode, the coating layer includes polymer particles, a dispersant, and a binder, the binder includes at least one selected from the group consisting of polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone (PVP), polyethylene (PE), polypropylene, ethylene-propylene-diene polymer, and sulfonated ethylene-propylene-diene polymer, and the binder may be included in an amount of 12% by weight to 32% by weight based on the total weight of the coating layer.
[0088] The electrode assembly of the other embodiment may not include a conventional polyolefin-based separator. Specifically, the electrode assembly may not include a conventional separator, but may include a coating layer disposed between a first electrode and a second electrode, as described with respect to the electrode of the first embodiment. For example, the first electrode and the second electrode may be formed to contact the coating layer, and no other layer may be interposed between the first and second electrodes and the coating layer.
[0089] The first electrode and the second electrode may be positive or negative, respectively. For example, when the first electrode is positive, the second electrode may be negative, and when the first electrode is negative, the second electrode may be positive. In this case, the positive electrode and the negative electrode are as described above.
[0090] The electrode assembly of the other embodiment may include a negative electrode, a coating layer formed on the negative electrode, and a positive electrode on which no coating layer is formed, or may include a positive electrode, a coating layer formed on the positive electrode, and a negative electrode on which no coating layer is formed.
[0091] Alternatively, the electrode assembly may have a configuration in which a coating layer formed on the negative electrode and a coating layer formed on the positive electrode are disposed in contact with each other, whereby excellent effects may be obtained in terms of stable charging and discharging due to improved electrical insulation.
[0092] <Lithium secondary battery> A lithium secondary battery including the above-mentioned electrode assembly will now be described.
[0093] Such a lithium secondary battery may include an electrode assembly and a flame-retardant electrolyte, where the electrode assembly is as described above.
[0094] At this time, the flame-retardant electrolyte is defined as including a flame-retardant solvent and a lithium salt having a flash point of 100°C or more or no flash point. At this time, the flame-retardant solvent may include a substantially non-flammable organic solvent having no flash point and an organic solvent having a high flash point of 100°C or more, or 100°C to 250°C, or 110°C to 200°C, and low volatility. The lithium secondary battery including the flame-retardant solvent and the lithium salt can exhibit excellent high-temperature safety. In addition, since the flame-retardant electrolyte can be uniformly impregnated into the coating layer including the polymer particles, the lithium secondary battery can achieve excellent electrochemical properties. The flash point defining the flame-retardant solvent can be measured by a closed or open method according to the standard method of ASTM D93 or ASTM D1310.
[0095] In a specific example, the flame-retardant solvent may be an organic solvent having a functional group that can contribute to the low volatility and flame retardancy or non-flammability of the organic solvent, for example, a functional group selected from the group consisting of a sulfone-based functional group, a fluorine-containing functional group such as a fluorine-substituted hydrocarbon group, a phosphorus-containing functional group such as a phosphate group or a phosphonate group, and a nitrile-based functional group, or one or more of such organic solvents may be mixed and used. More specifically, the flame-retardant solvent may include one or more organic solvents selected from the group consisting of a sulfone-based compound, a nitrile-based compound, a phosphoric acid-based compound, and a fluorine-substituted carbonate-based compound.
[0096] Among these, the sulfone-based compound may be a cyclic sulfone-based compound or a linear sulfone-based compound, and specifically may include one or more selected from the group consisting of sulfolane, ethyl methyl sulfone, dibutyl sulfone, ethyl vinyl sulfone, methyl propyl sulfone, ethyl-i-propyl sulfone, ethyl-i-butyl sulfone, i-propyl-i-butyl sulfone, i-propyl-s-butyl sulfone, and butyl-i-butyl sulfone.
[0097] The nitrile compound may include at least one selected from the group consisting of malononitrile, succinonitrile, glutaronitrile, adiponitrile, suberonitrile, and sebaconitrile.
[0098] Furthermore, the phosphoric acid compound may include at least one selected from the group consisting of dimethyl methyl phosphate, trimethyl phosphate, triethyl phosphate, tributyl phosphate, diethyl ethyl phosphate, dimethyl methyl phosphate, dimethyl (2-methoxyethoxy) methyl phosphonate, diethyl (2-methoxyethoxy) methyl phosphonate, and triphenyl phosphate.
[0099] In addition, the fluorine-substituted carbonate compound is bis(2,2,3,3-tetrafluoropropyl)carbonate, methyl-2,2,2-trifluoroethyl carbonate, ethyl-2,2,2-trifluoroethyl carbonate, propyl-2,2,2-trifluoroethyl carbonate, methyl-2,2,2,2',2',2'-hexafluoro-i-propyl carbonate, ethyl-2,2,2,2',2',2'-hexafluoro-i -propyl carbonate, di-2,2,2-trifluoroethyl carbonate, 2,2,2-trifluoroethyl-N,N-dimethyl carbonate, hexafluoro-i-propyl-N,N-dimethyl carbonate, 4-(2,2,3,3-tetrafluoropropoxymethyl)-[1,3]-dioxolan-2-one, and bis(2,2,3,3-pentafluoropropyl) carbonate.
[0100] On the other hand, the lithium salt contained in the flame-retardant electrolyte is used as a medium for transferring ions in a lithium secondary battery. The lithium salt contains, for example, Li as a cation. + The anion is F. - , Cl - , Br - , I - , NO3 - , N(CN)2- , BF4 - , ClO4 - , B 10 Cl 10 - , AlCl4 - , AlO2 - , PF6 - , CF3SO3 - , CH3CO2 - , CF3CO2 - , AsF6 - , SbF6 - , CH3SO3 - , (CF3CF2SO2)2N - , (CF3SO2)2N - , (FSO2)2N - , BF2C2O4 - , BC4O8 - , PF4C2O4 - , PF2C4O8 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , C4F9SO3 - , CF3CF2SO3 - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , CF3(CF2)7SO3 - and SCN - At least one selected from the group consisting of:
[0101] Specifically, the lithium salt is LiCl, LiBr, LiI, LiBF4, LiClO4, LiB 10 Cl 10, LiAlCl4, LiAlO2, LiPF6, LiCF3SO3, LiCH3CO2, LiCF3CO2, LiAsF6, LiSbF6, LiCH3SO3, LiFSI (lithium bis(fluorosulfonyl)imide, LiN(SO2F)2), LiBETI (lithium bis(perfluoroethanesulfonyl)imide, LiN(SO2CF2CF3)2) and LiTFSI (lithium bis(trifluoromethanesulfonyl)imide, LiN(SO2CF3)2), but from the perspective of excellent safety, it is preferable to contain LiN(SO2CF3)2.
[0102] In addition to these, lithium salts that are usually used as electrolytes for lithium secondary batteries can be used without any restrictions.
[0103] The concentration of the lithium salt can be appropriately changed within a range that is normally usable, but in order to obtain an optimal effect of forming a coating for preventing corrosion on the electrode surface, the lithium salt may be contained in the flame-retardant electrolyte at a concentration of 0.5 M to 6 M, or 1 M to 3 M, or 1 M to 2.5 M. When the concentration of the lithium salt satisfies the above range, the effect of improving the cycle characteristics of the lithium secondary battery during high-temperature storage is sufficient, and the viscosity of the flame-retardant electrolyte is appropriate, thereby improving the impregnation of the flame-retardant electrolyte.
[0104] The lithium secondary battery may be manufactured by forming an electrode assembly by disposing a coating layer between a positive electrode and a negative electrode, placing the electrode assembly in a cylindrical battery case or a prismatic battery case, and then injecting the flame-retardant electrolyte. Alternatively, the electrode assemblies may be stacked, and the resulting product obtained by impregnating the stack with the flame-retardant electrolyte may be placed in a battery case and sealed.
[0105] The battery case may be one commonly used in the art, and may have any shape depending on the intended use of the battery, such as, but not limited to, a cylindrical shape, a square shape, a pouch shape, or a coin shape.
[0106] The lithium secondary battery can be used not only as a battery cell used as a power source for a small device, but also as a unit battery for a medium- to large-sized battery module including a large number of battery cells. Preferred examples of the medium- to large-sized device include an electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, and an energy storage system (ESS).
[0107] The present invention will be described in more detail with reference to the following specific examples. However, the following examples are merely illustrative for understanding the present invention and are not intended to limit the scope of the present invention. It is obvious to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical ideas of the present description, and it is natural that such changes and modifications fall within the scope of the appended claims.
[0108] Examples and Comparative Examples First, in the following examples, the zeta potential of the polymer particles was measured by electrophoretic light scattering using a dynamic light scattering device (product name: ELS-Z) with the polymer particles dispersed in an aqueous solvent at a concentration of 0.1% by weight or less at a temperature of 25°C.
[0109] In addition, the flash point of the (flame-retardant) organic solvent contained in the (flame-retardant) electrolyte was measured by a closed-cup method according to the standard method of ASTM D93. Specifically, a sample container was filled with an organic solvent sample, the container was covered and sealed, and the sample container was heated at a constant rate according to the standard method. During heating, the sample container was periodically opened to check whether a flame was generated, and the temperature at the time of flame generation was measured as the flash point.
[0110] Example 1 (1) Preparation of composition for forming electrode coating layer It has a zeta potential of -50 mV and an average particle size of D 50 A composition for forming an electrode coating layer was prepared by dispersing 1 μm-sized polymethyl methacrylate (PMMA) polymer particles, hydrogenated nitrile rubber (H-NBR) dispersant, and polyvinylidene fluoride (PVDF) binder in an N-methyl-2-pyrrolidone (NMP) solvent in a weight ratio of 7:1:2. The solid content of the composition for forming an electrode coating layer was 21 wt %, and the viscosity at 25° C. was 6000 cP.
[0111] (2) Manufacturing of negative electrodes Next, a copper (Cu) metal thin film having a thickness of 20 μm was prepared as a negative electrode current collector, and a 55 μm negative electrode active material layer containing artificial graphite as a negative electrode active material was formed on one surface of the copper metal thin film. Then, the composition for forming an electrode coating layer was coated on the negative electrode active material layer and dried to form a coating layer having a thickness of 30 μm on the negative electrode active material layer, thereby manufacturing a negative electrode.
[0112] (3) Manufacture of lithium secondary batteries Li(Ni 0.8 Mn 0.1 Co 0.1 ) A 60 μm positive electrode containing O2 was prepared.
[0113] The coating layer of the negative electrode prepared as described above was placed in contact with the positive electrode to prepare an electrode assembly.
[0114] A flame-retardant electrolyte was prepared by dissolving LiN(SO2CF3)2 (LiTFSI) in a flame-retardant solvent, sulfolane (flash point: about 165°C), to a concentration of 1.5 M. The electrode assembly was placed in a battery case, and the flame-retardant electrolyte was poured into the battery case to prepare a lithium secondary battery.
[0115] Example 2 It has a zeta potential of -50 mV and an average particle size of D50 A composition for forming an electrode coating layer was prepared in the same manner as in Example 1, except that a polymethyl methacrylate (PMMA) polymer particle having a diameter of 1 μm, a hydrogenated nitrile rubber (H-NBR) dispersant, and a polyvinylidene fluoride (PVDF) binder were dispersed in an N-methyl-2-pyrrolidone (NMP) solvent in a weight ratio of 6:1:3 to prepare a composition for forming an electrode coating layer. At this time, the solid content of the composition for forming an electrode coating layer was 21 wt %, and the viscosity at 25° C. was 6200 cP.
[0116] A negative electrode and a lithium secondary battery were manufactured in the same manner as in Example 1, except that the composition for forming an electrode coating layer was used.
[0117] Comparative Example 1 A composition for forming an electrode coating layer was prepared in the same manner as in Example 1, except that the polymethyl methacrylate (PMMA) polymer particles and the polyvinylidene fluoride (PVDF) dispersant were mixed in a weight ratio of 9:1 without using a hydrogenated nitrile rubber (H-NBR) dispersant. The solid content of the composition for forming an electrode coating layer was 21 wt %, and the viscosity at 25° C. was 6500 cP.
[0118] A negative electrode and a lithium secondary battery were manufactured in the same manner as in Example 1, except that the composition for forming an electrode coating layer was used.
[0119] Comparative Example 2 Except for using polytetrafluoroethylene (PTFE) as a binder, a composition for forming an electrode coating layer was prepared in the same manner as in Example 1. At this time, the solid content of the composition for forming an electrode coating layer was 21 wt %, and the viscosity at 25° C. was 6600 cP.
[0120] A negative electrode and a lithium secondary battery were manufactured in the same manner as in Example 1, except that the composition for forming an electrode coating layer was used.
[0121] Comparative Example 3 (1) Manufacturing of negative electrodes A negative electrode was manufactured in the same manner as in Example 1, except that, unlike Example 1, no coating layer was formed on the negative electrode active material layer.
[0122] (2) Manufacture of lithium secondary batteries Li(Ni 0.8 Mn 0.1 Co 0.1 ) A 60 μm positive electrode containing O2 was prepared.
[0123] A lithium secondary battery was manufactured in the same manner as in Example 1, except that a separator made of polyolefin was interposed between the negative electrode and the positive electrode to manufacture an electrode assembly.
[0124] Experimental Example 1 - Coating properties evaluation of coating layer The surfaces of the inner-electrode coating layers produced in Examples 1 and 2 and Comparative Examples 1 and 2 were photographed and are shown in FIGS. 1 to 4.
[0125] Specifically, FIG. 1 is a photograph of the surface of the intra-electrode coating layer produced in Example 1, FIG. 2 is a photograph of the surface of the intra-electrode coating layer produced in Example 2, FIG. 3 is a photograph of the surface of the intra-electrode coating layer produced in Comparative Example 1, and FIG. 4 is a photograph of the surface of the intra-electrode coating layer produced in Comparative Example 2.
[0126] The surface of the coating layer was visually observed to determine whether or not cracks were present, and the results are shown in Table 1 below.
[0127] O: Cracks are present on the surface of the coating layer. X: No cracks on the surface of the coating layer
[0128] [Table 1]
[0129] As shown in Table 1 and FIGS. 1 to 4, it was confirmed that the coating layer included in the electrode of Comparative Example 1, which did not use a dispersant (H-NBR), had cracks on the surface, unlike the coating layers included in the electrodes of Examples 1 and 2.
[0130] In addition, it was confirmed that the coating layer included in the electrode of Comparative Example 2, which used polytetrafluoroethylene (PTFE) instead of polyvinylidene fluoride (PVDF) as the binder, had cracks on the surface, unlike the coating layers included in the electrodes of Examples 1 and 2.
[0131] Experimental Example 2: Evaluation of life characteristics of lithium secondary batteries The lithium secondary batteries prepared in Examples 1 and 2 were charged and discharged at 0.1C in a CC / CV charging mode with an upper limit voltage of 4.2V and in a CC discharging mode with a lower limit voltage of 3V, and then charged and discharged at 0.2C / 0.2C from 4.2V to 3V for 500 cycles, and the capacity retention was measured at intervals of 100 cycles. The measurement results are shown in Table 2 below and FIG. 5. FIG. 5 is a graph showing the capacity retention of the lithium secondary batteries including the electrodes prepared in Examples 1 and 2.
[0132] [Table 2]
[0133] As shown in Table 2 and FIG. 5, it was confirmed that both the lithium secondary batteries of Example 1 and Example 2 exhibited excellent capacity retention and life characteristics up to 200 cycles.
[0134] Going one step further, it can be seen that in Example 1, in which the binder content is 20 wt % relative to the total weight of the coating layer, the battery capacity retention rate after 200 cycles is more excellent than in Example 2, in which the binder content is 30 wt % relative to the total weight of the coating layer.
[0135] Experimental Example 3: High temperature safety evaluation of lithium secondary batteries The results of a hot box test on each of the lithium secondary batteries manufactured in Example 1 and Comparative Example 3 are shown in Table 3 below. Specifically, the hot box test was performed by increasing the temperature from 25° C. at a rate of 5° C. / min, holding the temperatures at 100° C., 120° C., 140° C., 150° C., 160° C., 170° C., and 180° C. for 30 minutes each, and then increasing the temperature to 200° C. at a rate of 2° C. / min. The ignition start temperatures are shown in Table 3 below.
[0136] On the other hand, in the case of the lithium secondary batteries produced from the negative electrodes of Comparative Example 1 and Comparative Example 2, charge / discharge performance was not exhibited from the initial stage of the cells, and therefore high temperature safety evaluation was omitted.
[0137] [Table 3]
[0138] As shown in Table 3, in the case of the lithium secondary battery using the anode of Example 1 instead of using a separator made of an existing polyolefin material, it can be seen that the high temperature safety is improved compared to the lithium secondary battery using the anode of Comparative Example 3 and a separator made of a polyolefin material.
Claims
1. An electrode comprising an electrode active material layer and a coating layer formed on the electrode active material layer, The coating layer includes polymer particles having an absolute value of a zeta potential of 25 mV or more; a dispersant; and a binder, The binder comprises at least one selected from the group consisting of polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone (PVP), polyethylene (PE), polypropylene, ethylene-propylene-diene polymers, and sulfonated ethylene-propylene-diene polymers; The binder is contained in an amount of 12 wt % to 32 wt % based on the total weight of the coating layer.
2. The electrode of claim 1 , wherein the polymer particles are contained in an amount of 55% to 85% by weight based on the total weight of the coating layer.
3. The electrode of claim 1 , wherein the dispersing agent comprises a hydrogenated nitrile-based polymer.
4. The electrode of claim 1 , wherein the dispersant is present in an amount of 3% by weight to 20% by weight based on the total weight of the coating layer.
5. The average particle diameter D of the polymer particles 50 The electrode of claim 1, wherein the thickness is 50 nm to 3 μm.
6. 2. The electrode of claim 1, wherein the polymer particles include at least one selected from the group consisting of polyethylene oxide (PEO), polyphenylene sulfide (PPS), polymethyl (meth)acrylate, polystyrene, polyvinyl chloride, polycarbonate, polysulfone, polyethersulfone, polyetherimide, polyphenylsulfone, polyamideimide, polyimide, polybenzimidazole, polyetherketone, polyphthalamide, polybutylene terephthalate, and polyethylene terephthalate.
7. The electrode of claim 1 , wherein the coating layer has a thickness of 5 μm to 50 μm and contains a plurality of pores having a diameter of 10 nm or greater.
8. A first electrode; A second electrode; a coating layer disposed between the first electrode and the second electrode, The coating layer includes polymer particles having an absolute value of a zeta potential of 25 mV or more; a dispersant; and a binder, The binder comprises at least one selected from the group consisting of polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone (PVP), polyethylene (PE), polypropylene, ethylene-propylene-diene polymers, and sulfonated ethylene-propylene-diene polymers; The binder is contained in an amount of 12 to 32 wt % based on the total weight of the coating layer.
9. The electrode assembly of claim 8, wherein the polymer particles are present in an amount of 55% to 85% by weight based on the total weight of the coating layer.
10. The electrode assembly of claim 8, wherein the dispersant is present in an amount of 3% to 20% by weight based on the total weight of the coating layer.
11. The average particle diameter D of the polymer particles 50 The electrode assembly according to claim 8, wherein the thickness is 50 nm to 3 μm.
12. 9. The electrode assembly of claim 8, wherein the polymer particles include at least one selected from the group consisting of polyethylene oxide (PEO), polyphenylene sulfide (PPS), polymethyl (meth)acrylate, polystyrene, polyvinyl chloride, polycarbonate, polysulfone, polyethersulfone, polyetherimide, polyphenylsulfone, polyamideimide, polyimide, polybenzimidazole, polyetherketone, polyphthalamide, polybutylene terephthalate, and polyethylene terephthalate.
13. The electrode assembly of any one of claims 8 to 12, wherein the coating layer has a thickness of 5 μm to 50 μm and includes a plurality of pores having a diameter of 10 nm or more, and the electrode assembly does not include a separator.
14. The electrode assembly of claim 8 , wherein the first electrode and the second electrode are in contact with the coating layer.
Citation Information
Patent Citations
Lithium secondary battery, separator for lithium secondary battery, electrode for lithium secondary battery, nonaqueous electrolyte for lithium secondary battery, and armor for lithium secondary battery
JP2008004441A
Dispersant composition for secondary battery slurry and use of the same
JP2017130399A
Secondary battery porous membrane, slurry for secondary battery porous membrane, and secondary battery
WO2012057324A1
Porous membrane for secondary cell, porous membrane slurry for secondary cell, nonconductive particles, electrode for secondary cell, separator for secondary cell, and secondary cell
WO2013147006A1